Habituation and memorization of spatial objects' configurations in mice from weaning to adulthood - Chapillon, P; Roullet, P (Behavioural processes, 1997)
This experiment investigated the development of habituation and memorization capacities of C57BL/6 mice. After a first session on a classic open field, four groups of subjects (3, 4, 5 and 9 weeks of age) were exposed to objects arranged in a pre-defined spatial environment during three exploratory sessions. Subsequently, for the test session, half of the mice was exposed to the previous situation, while the other half was exposed to a novel situation with a different spatial configuration for testing animal's abilities to detect and react to a change in their environment. Analysis showed age-related differences in behavioural habituation patterns. Moreover, contrary to our expectancy based on previous studies, the youngest mice (3 week-old) didn't exhibit significant renewal of exploration of the displaced objects during the test session. This results indicated that the youngest mice react differently than the adult mice when they are confronted to a novel environment and especially seem enable to construct a long-lasting representation of their environment when this representation concerns proximal information. The results are discussed in relation to previous studies conducted on the radial maze and the Morris water maze and it seems that the abilities of the youngest mice to construct a representation of their environment are partially dependent upon the type of information available (i.e. proximal versus distal information).